2021
DOI: 10.3390/ijms22105338
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism in THRA Resistance: The First Disease-Associated Variant Leading to an Increased Inhibitory Function of THRA2

Abstract: The nuclear thyroid hormone receptors (THRs) are key mediators of thyroid hormone function on the cellular level via modulation of gene expression. Two different genes encode THRs (THRA and THRB), and are pleiotropically involved in development, metabolism, and growth. The THRA1 and THRA2 isoforms, which result from alternative splicing of THRA, differ in their C-terminal ligand-binding domain (LBD). Most published disease-associated THRA variants are located in the LBD of THRA1 and impede triiodothyronine (T3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…In contrast to all other studies, we recently reported a THRA mutation that resulted in a gain-of-function in both isoforms 23 . A mutated glutamate-to-glycine residue in the first helix of the LBD had a promoting effect on T3-inducible TRα1 activity but also resulted in a gain-of-antagonistic effect for TRα2.…”
contrasting
confidence: 95%
See 1 more Smart Citation
“…In contrast to all other studies, we recently reported a THRA mutation that resulted in a gain-of-function in both isoforms 23 . A mutated glutamate-to-glycine residue in the first helix of the LBD had a promoting effect on T3-inducible TRα1 activity but also resulted in a gain-of-antagonistic effect for TRα2.…”
contrasting
confidence: 95%
“…Recently, we described a novel heterozygous point mutation that enhances the function of both TRα isoforms, TRα1 and TRα2 leading to increased T3-activation of TRα1 and increased antagonism of TRα2 [23]. This novel mechanism in RTH due to THRA mutations brings the TRα2 splice variant into focus and raises further interest in its physiological function.…”
mentioning
confidence: 99%
“…Moreover, the C-terminal domain of α2 was demonstrated to be sufficient for the inhibition of transactivation mediated by the estrogen receptor without requiring the N-terminal DBD [58], but it does not inhibit the binding of TRα1 to TREs [59]. Additionally, a recent study revealed a mutation in a patient, affecting both TRα1 and TRα2 [76]. This point mutation is located outside the DBD and enhances the DNE of TRα2, suggesting enhanced cofactor binding rather than affecting DNA binding [76].…”
Section: Molecular Functions Of Trα2 In Th Signallingmentioning
confidence: 99%
“…Most of these are located in the ligand binding domain of the carboxyl terminal portion of THRA1, causing a receptor loss of function, i.e., inability to bind the active form of TH, triiodothyronine (T3). Paisdzior et al [ 2 ] described a new variant of THRA located between the DNA and the ligand binding domain, thus affecting both THRA1 and THRA2. Interestingly, patients carrying this variant experience symptoms of hypo- and hyper-thyroidism.…”
mentioning
confidence: 99%